Peer relations and tensions in the school life of Finnish and Korean students: a cross-cultural perspective - Junghyun Yoon (Routledge, Taylor & Francis Group, 2022)
Drawing on cross-cultural qualitative research in comprehensive (primary and middle) schools in Finland and Korea, this article explores students’ peer relationships as well as tensions and negotiations that occur between student agency and school control. Based on school observations and interviews with students and teachers, this article illuminates the meaning of friendship and patterns of peer interactions among students, both within and between genders. It also reveals how school control and student agency manifest in the issues of space, time, and appearance. The findings imply that students develop gendered identities and roles through peer relations and socialisation in school. This article also interprets sociocultural uniqueness and commonality concerning interdependency and independency observed in peer relationships. Finally, the article illustrates that while control over the appearance of students seems to be different in each country, the students’ school lives are tightly controlled by regulations of time and space in both countries.